The role of arbuscular mycorrhizal symbiosis in plant abiotic stress - Wang, Qian; Liu, Mengmeng; Wang, Zhifan; Li, Junrong; Liu, Ke; Huang, Dong (Frontiers in Microbiology, 2024)
Arbuscular mycorrhizal fungi (AMF) can penetrate plant root cortical cells, establish a symbiosis with most land plant species, and form branched structures (known as arbuscules) for nutrient exchange. Plants have evolved a complete plant-AMF symbiosis system to sustain their growth and development under various types of abiotic stress. Here, we highlight recent studies of AM symbiosis and the regulation of symbiosis process. The roles of mycorrhizal symbiosis and host plant interactions in enhancing drought resistance, increasing mineral nutrient uptake, regulating hormone synthesis, improving salt resistance, and alleviating heavy metal stress were also discussed. Overall, studies of AM symbiosis and a variety of abiotic stresses will aid applications of AMF in sustainable agriculture and can improve plant production and environmental safety.